Que festa deve ser essa? : os conflitos sobre a organização do Carnaval de Belo Horizonte em 2019 na perspectiva do poder público, da imprensa e de blocos de rua - Amanda dos Santos Rodrigues (2021)
This paper aims to verify the meanings that different social agents such as street blocks organizers, sectors of the public power and press segments attributed to the idea of organizing the Belo Horizonte Carnival in 2019. Such gestures will be examined based on the concept of Organizational Communication, understood as the “process of conception and dispute of meanings in organizational relations” (BALDISSERA, 2008). We start from the understanding that the Carnival’s audiences emerge and propose meanings for the party’s organization, and realize that this is a process developed with interlocutors who dispute and tension in the ways of seeing and proposing the “new” city Carnival. To this end, we assemble some scenarios of negotiation and conflict in which we could perceive this dispute of meanings between the different audiences in the organization of the event.